Serum carotenoid and tocopherol concentrations and risk of asthma in childhood: a nested case–control study. Issue 3 (March 2017) - Hämäläinen, N.; Nwaru, B. I.; Erlund, I.; Takkinen, H.‐M.; Ahonen, S.; Toppari, J.; Ilonen, J.; Veijola, R.; Knip, M.; Kaila, M.; Virtanen, S. M.
Summary: Background: The antioxidant hypothesis regarding the risk of asthma in childhood has resulted in inconsistent findings. Some data indicate that the role of antioxidants in childhood asthma risk may have a critical time window of effect, but only a well‐designed longitudinal cohort study can clarify this hypothesis. Objective: To study the longitudinal associations between serum carotenoid and tocopherol concentrations during the first 4 years of life and asthma risk by the age of 5 years. Methods: Based on a case–control design nested within a Finnish birth cohort, 146 asthma cases were matched to 270 controls on birth time, sex, genetic risk, and birth place. Non‐fasting blood samples were collected at the ages of 1, 1.5, 2, 3, and 4 years and serum carotenoids and tocopherols were analysed. Parents reported the presence and age at start of persistent doctor‐diagnosed asthma in the child at the age of 5 years. Data analyses were conducted using generalized estimating equations. Results: We did not find strong associations between serum carotenoids and tocopherols and the risk of asthma based on age‐specific and longitudinal analyses. Both lower and higher quarters of α‐carotene and γ‐tocopherol increased the risk of asthma. Conclusions: The current findings do not support the suggestion that the increased prevalence of asthma may be a consequence of decreased intake of antioxidant nutrients. Moreover, we did not confirm any critical time window of impact of antioxidants on asthma risk. Replication of these findings in similar longitudinal settings will strengthen this evidence base.